Impact of smokeless tobacco-associated bacteriome in oral carcinogenesis. (August 2021) - Sajid, Mohammad; Srivastava, Sonal; Joshi, Lata; Bharadwaj, Mausumi
Abstract: Smokeless tobacco products possess a complex community of microorganisms. The microbial community ferment compounds present in the smokeless tobacco products and convert them into carcinogens like tobacco-associated nitrosamines. However, the potential of smokeless tobacco products associated bacteriome to manipulate systemic inflammation and other signaling pathways involved in the etiology of oral cancer will be a risk factor for oral cancer. Further, damage to oral epithelial cells causes a leaky oral layer that leads to increased infiltration of bacterial components like lipopolysaccharide, flagellin, and toxins, etc. The consumption of smokeless tobacco products can cause damage to the oral layer and dysbiosis of oral microbiota. Hence, the enrichment of harmful microbes due to dysbiosis in the oral cavity can produce high levels of bacterial metabolites and provoke inflammation as well as carcinogenesis. Understanding the complex and dynamic interrelation between the smokeless tobacco-linked bacteriome and host oral microbiome may help to unravel the mechanism of oral carcinogenesis stimulated by smokeless tobacco products. This review provides an insight into smokeless tobacco product-associated bacteriome and their potential in the progression of oral cancer. In the future, this will guide in the evolution of prevention and treatment strategies against smokeless tobacco products-induced oral cancer. Besides, it will assist the government organizations for better management and cessation policy building for the worldwide problem of smokeless tobacco addiction. Highlights: Bacteriome of STPs and their potential to synthesize tobacco-specific carcinogens. STPs-associated bacteriome can induce oral dysbiosis and provoke chronic inflammation. Mechanism of oral carcinogenesis induced by smokeless tobacco-linked bacteriome. Identification of potential carcinogenic microbes present in STPs needed to investigate.